Demodex galagoensis sp. nov. (Acariformes: Demodecidae) from the Senegal bushbaby Galago senegalensis in the light of the current understanding of the demodecid mite fauna of primates, with notes on a case report - Joanna N. Izdebska; Leszek Rolbiecki; Łukasz Skomorucha (International Journal for Parasitology: Parasites and Wildlife)
The Demodecidae fauna of primates is very poorly known, not only with regard to its host range, but also the possibility of the co-occurrence of different mite species in individual host species. So far, only seven species, from five host species, have been described from primates, including five species identified in three species from the suborder Haplorrhini, including Demodex brevis, D. folliculorum, which are associated with humans, in whom they can cause various disease symptoms. The three remaining species have been found only once in captivity: in the rhesus macaque Macaca mulatta, the Guianan squirrel monkey Saimiri sciureus and the red-handed tamarin Saguinus midas. However, two species were found in one representative of the suborder Strepsirrhini, the moholi bushbaby Galago moholi from Rwanda. A new species, Demodex galagoensis sp. nov, has now been described from the Senegal bushbaby Galago senegalensis, kept as a pet; the demodecid mites caused disease symptoms in the skin of the head. Studies highlight the importance of coordinating veterinary examinations with correct identification and taxonomic analyses; such an approach contributes new data to our understanding of biodiversity, and consequently, correct identification is an important factor in the development of effective treatment methods.